Clinical profile and outcomes of endoscopic surgery patients during a mobile gynecological surgery program in low- and middle-income communities in Kenya (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Access to quality gynecological surgery in low- and middle-income communities has beengreatly hampered by logistical and socioeconomic challenges. These challenges can be overcomethrough the provision of mobile laparoscopic surgery. Endoscopic surgery reduces the rate of infection,duration of hospital stay, and the need for blood transfusion, which are factors attributable to surgicaldisease burden due to poverty. A team comprising gynecologists, nurses, and theater technicians hasbeen providing laparoscopic surgery to patients in low-income communities in Kiambu, Nairobi, and Merucounties in Kenya. This initiative was undertaken by pooling resources to procure basic laparoscopicequipment, a regional needs assessment for gynecological surgery, and logistical planning for outpatientclinical services. This was followed by the provision of laparoscopic surgery to patients diagnosed withvarious gynecological conditions. We present programmatic data of the clinical profile and outcomes ofpatients who benefited from the program.Results: A total of 175 women benefited from the program from January 2023 to December 2023. Themost common surgery undertaken was laparoscopic hysterectomy due to symptomatic uterine fibroids.Other procedures included diagnostic hysteroscopy and laparoscopy for chronic pelvic pain. Most womenwere under the national health insurance fund scheme.Conclusion: The program has improved the quality of services provided and demonstrated the feasibilityof mobile surgical workshops as an intervention to improve the quality of services in low-incomecommunities.